The effect of antiplatelet drugs on the management of cardiovascular diseases - Boralkar, Rohan R.; Nilamwar, Shweta S.; Mane, Pranjali P.; Giri, Ashok B. (International Journal of Research in Medical Sciences, 2025)
Cardiovascular diseases (CVDs) are the leading global cause of mortality, necessitating innovative strategies for prevention, diagnosis, and treatment. Antiplatelet drugs play a vital role in mitigating adverse atherothrombotic events by inhibiting platelet aggregation, crucial for managing conditions such as myocardial infarction, ischemic stroke, and peripheral artery disease. Platelets, essential for haemostasis, also contribute to thrombus formation in vascular injury and disease. Their activation is triggered by stimuli like collagen, thrombin, and adenosine diphosphate (ADP). Antiplatelet drugs target these pathways to prevent arterial thrombosis. Key classes of antiplatelet agents include cyclooxygenase inhibitors, P2Y12 receptor antagonists, glycoprotein IIb/IIIa inhibitors, and phosphodiesterase inhibitors. Aspirin, a COX-1 inhibitor, irreversibly blocks thromboxane A2 production, effectively reducing recurrent cardiovascular events, though its role in primary prevention is tempered by bleeding risks. P2Y12 inhibitors, such as clopidogrel, prasugrel, and ticagrelor, suppress ADP-mediated platelet activation, with newer agents providing consistent efficacy but higher bleeding risk. Dual antiplatelet therapy, combining aspirin and a P2Y12 inhibitor, is the standard for acute coronary syndrome and post-PCI management. Challenges, including bleeding and resistance, underscore the need for personalized approaches using pharmacogenomics. Ongoing research aims to develop safer, targeted therapies, including thrombin receptor blockers and novel combination regimens.